Social trust and electoral populism: Explaining the quality of government - Philip Keefer; Carlos G. Scartascini; Razvan Vlaicu (Inter-American Development Bank (IDB), 2019)
Voters would be better off if they removed politicians offering low-quality government by pursuing populist policies and re-elected those who improved government quality with sustainable policies. In many political contexts, including those with free and fair elections, voters do the opposite. Low social trust can account for this paradox: voters must act collectively to shape political incentives, but low trust among voters is an obstacle to collective action. If every voter believes that fellow voters will accept particularistic benefits from poorly performing governments that keep them from voting against those governments, no voter has an incentive to select politicians who promise high-quality government. By the same logic, low social trust prevents voters from sanctioning politicians who renege on their promises. Frequent reneging on campaign promises, in turn, leads voters to hold low political trust. Low quality government, and in particular populism, emerge as optimal electoral strategies of political candidates in this environment. We analyze new survey data from 5,800 respondents in seven Latin American countries that provides support for a novel argument about populism and the quality of government: voters who express low trust are significantly more likely to prefer populist policies that reflect a low quality of government.
Keywords: D72; H41; 330; Trust; Collective action; Populism; Quality of government